1985
DOI: 10.1038/clpt.1985.197
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term therapy with naltrexone on body weight in obesity

Abstract: The endogenous opiate system is thought to be associated with the regulation of food intake and body weight. Opiate antagonists decrease food intake in animals, but there are no controlled studies in obese man to evaluate body weight response to naltrexone. Sixty obese people were randomized into three groups and given 0, 50, or 100 mg of the opiate antagonist naltrexone for 8 weeks in an outpatient, double-blind study. Weight loss was not significant in either the 50 or 100 mg groups as compared with placebo.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
2

Year Published

1988
1988
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(63 citation statements)
references
References 1 publication
2
59
0
2
Order By: Relevance
“…Interestingly, the inhibitory effects of opioid receptor antagonists on food intake and body weight appear most pronounced in obese animals or when animals are fed a highly palatable diet (12,19). Similar inhibitory effects on appetite are observed clinically in humans treated with the opioid receptor antagonist naloxone, naltrexone, or nalmefene; however, body weight does not appear to be consistently affected by these treatments (3,18,26).…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…Interestingly, the inhibitory effects of opioid receptor antagonists on food intake and body weight appear most pronounced in obese animals or when animals are fed a highly palatable diet (12,19). Similar inhibitory effects on appetite are observed clinically in humans treated with the opioid receptor antagonist naloxone, naltrexone, or nalmefene; however, body weight does not appear to be consistently affected by these treatments (3,18,26).…”
mentioning
confidence: 74%
“…Subjective ratings of reward-related aspects of food palatability appear to be most related to the inhibitory effects of opioid antagonists on appetite in humans (46). Unfortunately, chronic treatment with opioid antagonists failed to produce consistent reductions in body weight clinically (3,18,26). The reason for the disparity between the acute effects of opioid receptor antagonists and chronic effects is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical experience with neutral opioid receptor antagonists, such as naltrexone, demonstrates that although suppression of short-term food intake is observed (Drewnowski, 1997), a significant impact on body weight is not (Atkinson et al, 1985;Malcolm et al, 1985). It has been suggested that opioid receptor inverse agonists may be more effective than neutral antagonists in the treatment of obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Naltrexone, um antagonista opióide de longa ação, foi utilizado em ensaios clínicos, com resultados frustrantes em baixa dose. O uso de doses mais elevadas associou-se a toxicidade hepática (138).…”
Section: B Peptídeos Opióides Endógenosunclassified